2012
DOI: 10.4103/1319-3767.103426
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of endoscopic ultrasound guided fine needle aspiration in patients with solid pancreatic neoplasms

Abstract: Background/Aim:Endosonography is a distinct method for evaluating the structural lesions of the gastrointestinal (GI) tract, particularly the pancreatobilliary region. This procedure has made a fundamental change in the diagnosis of pancreatic mass lesion through providing fine needle aspiration. This study aims at evaluating the results and efficacy of endoscopic ultrasound fine needle aspiration (EUS-FNA) in patients with pancreatic solid mass.Patients and Methods:The present study is an observational, prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…The role of EUS‐FNA is debated in potentially resectable pancreatic tumors . It is, however, considered useful to help differentiate benign neoplasms or lesions that mimic pancreatic cancer and to assist with surgical planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of EUS‐FNA is debated in potentially resectable pancreatic tumors . It is, however, considered useful to help differentiate benign neoplasms or lesions that mimic pancreatic cancer and to assist with surgical planning.…”
Section: Discussionmentioning
confidence: 99%
“…The role of EUS-FNA is debated in potentially resectable pancreatic tumors. [16][17][18][19] It is, however, considered useful to help differentiate benign neoplasms or lesions that mimic pancreatic cancer and to assist with surgical planning. In a large prospective study of 103 consecutive patients with resectable pancreatic lesions, 20 three patients with solid pancreatic masses highly suspicious for malignancy underwent surgical resection despite a negative EUS-FNA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in most cases it is possible to avoid unnecessary surgical interventions in advanced pancreatic cancer, and EUS is considered the preferred method for loco-regional staging of pancreatic cancer. A medical literature review to evaluate the role of EUS-FNA for diagnosis of solid pancreatic masses showed a 78%-95% sensitivity, 75%-100% specificity, and 78%-95% accuracy,17222324252627282930313233 confirming that EUS-FNA is an effective and safe method to obtain a cytological diagnosis of pancreatic tumors 30…”
Section: From the Pastmentioning
confidence: 94%
“…Other advantages of EUS include accurate assessment of peripancreatic nodal disease and allowance of tumor biopsy by fine-needle aspiration (FNA). [ 10 11 ] However ductal adenocarcinomas can elicit a strong desmoplastic reaction in some cases that is responsible for hard consistency of the tumor and sampling error in EUS-FNA.…”
Section: Introductionmentioning
confidence: 99%